Teknologi Penyimpanan Telur Ayam Konsumsi Menggunakan Ekstrak Etanol Daun Jati dan Lemak Abdomen Ayam yang Direndering - Siswara, Hamzah Nata; Firdaus, Moh Fachrul Haman; Saputro, Tri Hadi; Huda, Khoirul (Universitas Bengkulu, 2025)
Eggs are nutritious livestock products and are easily digested by the human body. The nutrients contained include minerals, vitamins, proteins, carbohydrates, and fats. This research was conducted to determine the effect of using teak leaf extract and chicken abdominal fat on weight loss, air cell, yolk, and albumen quality during storage. The treatments were divided into 4, namely P0 (control), P1 (teak leaf extract), P2 (chicken abdominal oil), and P3 (teak leaf extract and chicken abdominal oil). This research was conducted for 20 days. The data was analyzed using a completely randomized design (CRD) factorial pattern with two factors, four treatments, and three replications. This research used Duncan's Multiple Range Test to test the different treatments. The results show significant differences (P<0.05) in egg weight loss, air cell, yolk index, albumen pH, yolk pH, albumen water content, and haugh unit. The best treatment after the 20th day of storage is P3 treatment. These results indicate that the combination treatment of teak leaf extract and chicken abdominal oil can be used as an egg storage technology.